Epidural Cystic Spinal Meningioma: A Case Report. Issue 11 (March 2016) - Zhang, Ji; Chen, Zheng-he; Wang, Zi-feng; Sun, Peng; Jin, Jie-tian; Zhang, Xiang-heng; Zhao, Yi-ying; Wang, Jian; Mou, Yong-gao; Chen, Zhong-ping
Abstract : Abstract: Cystic spinal meningioma (CSM) is an uncommon meningioma variant. Extradural CSMs are particularly rare and difficult to distinguish from other intraaxial tumors. This study presents a case of a 36-year-old woman with intraspinal extradual CSM at the thoracolumbar spine. She experienced persistent weakness, progressive numbness, and sensory disturbance in the right lower limb. Magnetic resonance imaging (MRI) of the patient revealed an irregular cystic mass at the thoracic 11 to lumbar 3 levels dorsally. This case was misdiagnosed as other neoplasms prior to surgery because of the atypical radiographic features and location of the tumor. Extradural CSMs should be considered in the differential diagnosis of intraspinal extradural cystic neoplasms. Complete removal of cystic wall provides an optimal outcome, rendering the lesion curable.